The Role of The Arab Society of Plant Protection in Enhancing Plant Health Research Coordination in The Arab Region - Kumari, Safaa; Makkouk, Khaled; Jboory, Ibrahim (The International Association for the Plant Protection Sciences, 2024)
The strategic objectives in plant health research and development in any country or region are achieved through (i) enhancement of understanding and knowledge of plant health issues and solutions, (ii) development of evidence based risk assessment policy approaches to empower delivery partners and practitioners to make solid decisions and take necessary action, (iii) develop and adopt innovations and new technologies in support of plant health policy objectives, and (iv) create high-quality plant health research capabilities. The Arab Society for Plant Protection (ASPP), can play an influential role in achieving some of the above mentioned objectives by enhancing collaboration among scientific groups from different Arab and Mediterranean countries through a variety of activities such as (i) organizing regional conferences that bring together scientists from different Arab countries and the rest of the world to shed light on significantly important plant health issues of common concern and publicize best pest management practices, (ii) organizing regional workshops addressing specific plant health issues that require joint effort, (iii) encourage and facilitate distribution of up-to-date knowledge related to crop health management, and (iv) enhance technical skills through specialized courses. In addition, ASPP can facilitate the formation and implementation of joint regional research projects that focus on plant health management. Furthermore, ASPP can play an essential role in identifying plant health challenges facing the Arab region and reflecting on future solutions that are needed to minimize yield losses caused by pests to enhance food security for future generations in the Arab region.